VOT and VOT ratio in connected speech in spanish speakers with Parkinson?s Disease - Camargo-Mendoza, Maryluz; Castillo-Triana, Nicolas; Orozco-Arroyave, Juan Rafael (Revista de Investigación en Logopedia, 2023)
The Voice Onset Time (VOT) is an acoustic measure that refers to the difference between the time of the release of the occlusion and the beginning of the vibration of the vocal cords in plosive sounds; the VOT ratio (VOTr), on the other hand, refers to the relationship between the VOT and the duration of the syllable that seeks to model the effect of the speech rate on the VOT. Both measures have been studied in speakers with Parkinson's Disease (PD) in experimental speech tasks, but there are few studies in people with PD who are Spanish speakers and in the context of connected speech. In this study, the behavior of VOT and VOTr in connected speech in Colombian Spanish speakers with PD was investigated. Using the Praat software, the VOT and VOTr of the sounds /p, b, t, d, k, g/ were calculated in recordings taken from the PC-GITA corpus corresponding to 50 people with PD and 50 without PD, matched by age and sex. It was found that, with some variations, the VOT and the VOTr in connected speech behave similarly to each other and with respect to VOT extracted from other speech stimuli previously studied; in contrast with people without PD, women with PD had a significative longer VOT with /p/ (p < 0.05), and men and women had a shorter VOT and VOTr (p <= 0.05), differences related to sex were found just in VOT of /p/ in women with PD. This evidence could indicate that in Spanish speakers, in connected speech, both measures (VOT and VOTr) are equally sensitive to changes in VOT associated with PD and that sex influence could be dismissed in most of the plosive phonemes.
CRIS-Team WoS Importer:2023-05-26